The outer membrane protease PgtE of Salmonella enterica interferes with the alternative complement pathway by cleaving factors B and H - Riva, Rauna; Korhonen, Timo K.; Meri, Seppo (Frontiers in Microbiology, 2015)
The virulence factor PgtE is an outer membrane protease (omptin) of the zoonotic pathogen Salmonella enterica that causes diseases ranging from gastroenteritis to severe enteric fever. It is surface exposed in bacteria that have a short-chain, i.e. rough LPS, as observed e.g. in bacteria residing inside macrophages or just emerging from them. We investigated whether PgtE cleaves the complement factors B (B) and H (H), key proteins controlling formation and inactivation of the complement protein C3b and thereby the activity of the complement system. S. enterica serovar Typhimurium or omptin-expressing recombinant E. coli bacteria were incubated with purified human complement proteins or recombinant H fragments. PgtE cleaved both B and H, whereas its close homolog Pla of Yersinia pestis cleaved only H. H was cleaved at both N- and C-termini, while the central region resisted proteolysis. Because of multiple effects of PgtE on complement components (cleavage of C3, C3b, B and H) we assessed its effect on the opsonophagocytosis of Salmonella. In human serum, C3 cleavage was dependent on proteolytically active PgtE. Human neutrophils interacted less with serum-opsonized FITC-stained S. enterica 14028R than with the isogenic ΔpgtE strain, as analyzed by flow cytometry. In conclusion, cleavage of B and H by PgtE, together with C3 cleavage, affects the C3-mediated recognition of S. enterica by human neutrophils, thus thwarting the immune protection against Salmonella.